Pengaruh Pemahaman Perpajakan, Kualitas Pelayanan Pajak, dan Sanksi Pajak pada Kepatuhan Wajib Pajak Orang Pribadi - I Kadek Gede Dhimas Kartika Saputra; I Nyoman Wijana Asmara Putra (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Tax is a source of state revenue with the largest contribution to the APBN. State revenue from taxes in Indonesia has not been carried out optimally compared to countries in the Asia-Pacific. The decline in tax revenue is caused by the low level of taxpayer compliance in paying taxes. This study aims to obtain empirical evidence regarding the effect of tax understanding, quality of tax services, and tax sanctions on individual taxpayer compliance at the Tabanan Pratama Tax Office. The theory used in this study is the Theory of Planned Behavior. The sampling method used is nonprobability sampling with incidental sampling techniques. The population in this study were individual taxpayers registered at the Tabanan Pratama Tax Office totaling 227,768 with a sample used of 100 respondents calculated using the slovin formula. Data collection using questionnaires, and analyzed using multiple linear regression techniques. The results of the study indicate that the quality of tax services and tax sanctions have a positive and significant effect on individual taxpayer compliance registered at the Tabanan Pratama Tax Office, but tax understanding does not affect individual taxpayer compliance registered at the Tabanan Pratama Tax Office.